Hood-building dynamics and mating mode in the temperate fiddler crab Uca uruguayensis Nobili, 1901 - Ribeiro, Pablo Damián (2016)
Courting males of 18 species of fiddler crabs (Uca Leach, 1814) are known to build mud or sand structures at the entrances of their burrows. Females orient to these structures when seeking mates and, in some species, males sometimes orient to their own structures as well to relocate their burrows. We studied hood building in the temperate species Uca uruguayensis Nobili, 1901, the southernmost fiddler crab species, which mates both underground in males' burrows, especially at high densities, and on the surface at the entrance to females' burrows, a more common mode at low densities. Uca uruguayensis is relatively inactive during the winter and it was expected that the intensity of hood building would vary seasonally, with more hoods built when underground mating was more common. Courting male U. uruguayensis built nearly symmetrical cupped hoods of muddy sand, approximately half as high and two-thirds as deep as wide. Male courtship and mating occurred in summer from November 2001 to January 2002, but hood building was largely restricted to the last semi-monthly cycle, when the maximum number of matings were coincident with the maximum occurrence of hoods. The predominance of hood building at the end of the season may reflect the amount of time following winter inactivity that males need to feed before they exceed a threshold in the trade-off between allocation of resources to growth or reproduction. Contrary to expectations, males built more hoods at low densities where inter-burrow distances were greater. Males more often build hoods at lower densities because hoods enable them to venture further from their burrows to court both passing and burrow resident females. The temporal pattern of hood building by male U. uruguayensis may therefore reflect the mechanisms courting males use to relocate their burrows as well as variation in the social and spatial context of courtship and mate choice.